1987
DOI: 10.1017/s0003356100018857
|View full text |Cite
|
Sign up to set email alerts
|

Breed and sex differences in equally mature sheep and goats 3. Muscle weight distribution

Abstract: Males and females from Soay, Welsh Mountain, Southdown, Finnish Landrace, Jacob, Wiltshire Horn and Oxford Down sheep breeds and a breed of feral goats were slaughtered when they reached 0-40, 0-52, 0-64 or 0-76 of the mean mature body weight of their breed and sex. Total weight of dissected muscle was close to 0-30 times fleece-free empty body weight, or 0-24 times live weight, for all breeds and stages of maturity. The growth of 12 individual muscles or muscle groups dissected from the commercially higher-va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 13 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…3) g/kg more of their muscle in the prime shoulder than did females and 19 (s.e. Similar results have been found in studies of individual muscles (Lohse, 1973;Jury et al, 1911;Thonney et al, 1987c). Secondary sex characteristics were also reflected in males containing 10 (s.e.…”
Section: Genetic Effects Of Sex and Breed On Mean Body Compositionsupporting
confidence: 87%
“…3) g/kg more of their muscle in the prime shoulder than did females and 19 (s.e. Similar results have been found in studies of individual muscles (Lohse, 1973;Jury et al, 1911;Thonney et al, 1987c). Secondary sex characteristics were also reflected in males containing 10 (s.e.…”
Section: Genetic Effects Of Sex and Breed On Mean Body Compositionsupporting
confidence: 87%
“…Meat proportions of the breast rib and neck did not change significantly ( Table 4), while that of the flank was a mirror image of changes in SCF (Table 2), by declining between fat scores 1 to 3 with no significant variation between fat scores 3 and 5. As a result of the high increase in SCF proportions over all fat scores, % meat in the loin declined significantly (P <0.05) between fat score 1 and 5 While some work has been reported on the proportional development of muscles in cattle (Berg & Butterfield (1978) and sheep (Lohse et al, 1971;Palsson & Verges, 1952;Thonney et al, 1987), it is difficult to relate these results with the yield of commercial cuts, since anatomical muscle grouping often extends over cuts or various groups are contained within a commercial cut. Moreover, meat and not muscle yield was reported in the present study and therefore IMF was included in the proportions reported.…”
Section: Resultsmentioning
confidence: 97%
“…The larger eye muscle areas in the Southdown cross lambs at a set carcass weight may be a reflection of the fact that this breed has been shown to have a slightly higher proportion of longissimus muscle to total muscle in comparisons where this breed was included (Taylor et al 1980;Thonney et al 1987). This muscle comprised 9.6% of muscle in the Southdown lambs and 7.7% in the Finn lambs.…”
Section: Discussionmentioning
confidence: 94%